The Divine Kuṟa Tribe : Kuṟavañci and other Prabandhams - Muilwijk, M., (Asian Studies - Book Archive pre-2000., 1996)
Poetry and music have always been important parts of Tamil literature and from early times, Tamil poetry has been sung. It is not surprising, therefore, to find a number of operatic genres in Tamil literature. One of these is 'kuṟavañci', which was especially popular in the seventeenth to nineteenth century. In kuṟavañci, poetry and music are combined with dance to form highly entertaining works, in which serious parts are interspersed with humorous ones. This study deals with this fascinating opera-form. It gives an account of the stories told in these operas and of the various embellishments used in telling them. There is a large section on the poetical and musical forms used, explaining their construction and analysing their use. Several examples of verses and songs are included.